No Better than a Criminal - Brundidge, Harry T. (Tufts Archival Research Center, 2006)
Harry Brundidge, of the Brundidge Crime Report, describes his friendships with criminals; his belief that criminals, like anyone else, have good qualities; his disappointment in the failure of some Christians to extend kindness towards ex-convicts; his gratitude for those Christians who have helped ex-convicts find jobs; and the satisfaction he receives from treating prisoners like people. Audio also contains an advertisement for "This I Believe" book, Volume II.